The earless monitor lizard Lanthanotus borneensis – a venomous animal? - Mebs, Dietrich (2021)
Based on its mandibular gland secretion, the earless monitor lizard, Lanthanotus borneensis, has been considered a venomous animal like other members of the Toxicofera group, including Heloderma. In the present study, the gland structure and teeth of L. borneensis were examined by micro-tomography (μCT) and scanning electron microscopy (SEM), respectively, and proteomic analysis of the gland extract was performed. The mandibular gland consists of six compartments with separate ducts. The pleurodont teeth of the lower and upper jaw are not grooved but possess a sharp ridge on the anterior surface. Proteomic analysis of the gland extract confirmed previous studies that kallikrein enzymes are the major biologically active components. In view of the lizard's biology, its mandibular gland secretion is obviously not needed for prey capture or defence. It seems not justified the labelling of L. borneensis as a venomous animal. However, definitively answering this question requires toxinological studies on natural prey.